2020
DOI: 10.4025/actasciagron.v42i1.43335
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive phenology of yellow pitaya in a high-altitude tropical region in Brazil

Abstract: Pitaya species cultivation in Brazil is recent, and information on the production of the species Selenicereus megalanthus, known as yellow pitaya, is non-existent because research in the country has focused on the species Hylocereus undatus. The research was carried out with the objective of evaluating the reproductive phenology of the species S. megalanthus, in a high-altitude climate conditions in Brazil. The study orchard of yellow pitaya was located at an altitude of 726 metres, 18º 04' 15" S latitude and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…The multivariate and cluster analyses showed that the cladode and fruit characteristics showed higher variability among the morphological traits (Figure 5a,b). Although many authors find positive results, morphological and agronomic characteristics used to measure genetic diversity in certain populations of individuals often do not allow identification of discrete taxonomic groups since most plant characteristics are influenced by environmental factors, exhibiting continuous variation and a high degree of phenotypic plasticity [28]. This study demonstrated that the natural populations of pitahaya from the five departments showed high variation in the morphological characteristics that were evaluated in situ.…”
Section: Discussionmentioning
confidence: 78%
“…The multivariate and cluster analyses showed that the cladode and fruit characteristics showed higher variability among the morphological traits (Figure 5a,b). Although many authors find positive results, morphological and agronomic characteristics used to measure genetic diversity in certain populations of individuals often do not allow identification of discrete taxonomic groups since most plant characteristics are influenced by environmental factors, exhibiting continuous variation and a high degree of phenotypic plasticity [28]. This study demonstrated that the natural populations of pitahaya from the five departments showed high variation in the morphological characteristics that were evaluated in situ.…”
Section: Discussionmentioning
confidence: 78%
“…Besides showing low vegetative vigor, S. megalanthus flowering season does not coincide with the that of the other species cultivated in the experimental area (Rabelo et al, 2020a). This fact may affect size and yield, since even being a selfcompatible species, pollen viability is reduced because S. megalanthus is a tetraploid plant (2n=44), with irregular meiosis occurring in anaphase I (Lichtenzveig et al, 2000).…”
Section: Resultsmentioning
confidence: 94%
“…Similar a lo señalado en otros estudios, que reportan entre 3-5 ciclos de floración por año en Hylocereus spp. (Nerd et al, 2002;Marques et al, 2011;Kishore, 2016;Martínez-Ruiz et al, 2017), y también para pitahaya amarilla S. megalanthus (Rabelo et al, 2020), pero inferior a lo documentado por otros investigadores, que encontraron entre 5 y 9 ciclos por año (Ángel et al, 2012;Silva et al, 2015;Osuna-Enciso et al, 2016). En una prueba con 30 genotipos de pitahaya realizada en Taiwán, el número de ciclos de floración varió entre tres y seis por año, según el genotipo (Ha et al, 2018).…”
Section: Discussionunclassified